Sprzedaż produktów rolnych jako działalność rolnicza w prawie włoskim - KAPAŁA, ANNA (WYDAWNICTWO NAUKOWE UNIWERSYTETU IM. ADAMA MICKIEWICZA, POZNAŃ, 2011)
The aim of the paper is to provide a more detailed characteristic of criteria determining the qualification of direct sale as related agricultural activity. Summing up the author presented conclusions concerning advantages and disadvantages of Italian regulations from the point of view of the agricultural entrepreneur, system cohesion and in the context of Polish regulations. The development of direct sale in case of agricultural products is definitely a desirable phenomenon both from the point of view of the agricultural entrepreneur and the consumer. The Italian regulations satisfy those needs. They contribute to a strengthening of the position of agricultural entrepreneurs, not only as producers, but also one of the important subjects in the agri-food sector. It realises the objective of “complete utilisation of the production cycle of an enterprise”, facilitating sales of agricultural products. At the same time the Italian regulations may be a perfect reference point for comparison with the fragmentary Polish regulations.

Lo scopo delle considerazioni è la caratteristica più particolareggiata dei criteri decisivi nel qualificare la vendita diretta nei termini di attività agricole connesse. Riassumendo, l’Autrice ha presentato le conclusioni sui vantaggi e gli svantaggi della regolazione italiana dal punto di vista degli imprenditori agricoli, della coerenza del sistema e anche sullo sfondo delle norme del diritto polacco. Lo sviluppo della vendita diretta dei prodotti agricoli è indubbiamente un fenomeno auspicabile dal punto di vista sia dell’imprenditore agricolo sia del consumatore. La regolazione italiana viene incontro a tali esigenze. Essa contribuisce a rafforzare la posizione dell’imprenditore agricolo, non solo in qualità di produttore, ma anche come uno dei principali protagonisti del settore agro-alimentare. Persegue anche l’obiettivo di „l’utilizzo complessivo del ciclo produttivo dell’impresa”, facilitando la vendita dei prodotti agricoli. Allo stesso tempo la regolazione italiana può essere un ottimo punto di riferimento per il confronto con la frammentata regolazione polacca.
Direct sale of agricultural products as agricultural activity in italian law
La vendita diretta dei prodotti agricoli come attività agricola nel diritto italiano